Petrorhagia dubia subsp. mustafanus (Caryophyllaceae), a new subspecies from Turkey - Oskay, Dilek (Phytotaxa, 2024)
Petrorhagia dubia subsp. mustafanus (Caryophyllaceae) is described as a new subspecies from Dede mountain in Soma (Manisa), west Anatolia, Turkey. Diagnosis, description, preferential habitat, distribution, conservation status, and original photographs are given, as well as a comparison with the similar P. dubia subsp. dubia is discussed.